Design and build a microsoft product or software for microsoft - Tan, Ronald Wee Jun (2018)
The motivation of this project is related to Singapore’s aging population where there will be more than 10% of Singapore population to be age 65 and above as of 2020. With Reference to TODAY [1], by Year 2050, it is projected that there will be at least 50% of the population to be age 65 and above. With this great amount of elderly population, Singapore’s government has constructed and increased healthcare facilities to meet the demands.